ANALISIS WACANA KRITIS NORMAN FAIRCLOUGH TERHADAP PEMBERITAAN BANJIR BANDANG SUMATERA UTARA 2025 DI KOMPAS.COM - Rahma Hidayati; Arlin Septia Basana Siagian; Nur Fatimah; Dia Ananda Putri; Poppy Amalia (STKIP Subang, 2026)
This study analyzes the representation of the 2025 North Sumatra flash flood disaster in Kompas.com news coverage using Norman Fairclough's Critical Discourse Analysis (CDA) approach. The data consists of five news articles published between November 26 and December 3, 2025. Analysis was conducted through three levels: textual analysis, discursive practice, and social practice. The findings reveal two dominant patterns in disaster representation. First, naturalization of disaster, evident in the November 26 and December 2, 2025 articles through the use of the word